(untitled) (American Journal of Technology and Applied Sciences, 2024)
The article presents the process of fphysical deposition of coatings in a vacuum, which consists of spraying a substance in a special vacuum chamber. As well as the main operations of a typical technological process for applying coatings using the PVD method.